2020
DOI: 10.5194/acp-20-4787-2020
|View full text |Cite
|
Sign up to set email alerts
|

Trends and emissions of six perfluorocarbons in the Northern Hemisphere and Southern Hemisphere

Abstract: Abstract. Perfluorocarbons (PFCs) are potent greenhouse gases with global warming potentials up to several thousand times greater than CO2 on a 100-year time horizon. The lack of any significant sinks for PFCs means that they have long atmospheric lifetimes of the order of thousands of years. Anthropogenic production is thought to be the only source for most PFCs. Here we report an update on the global atmospheric abundances of the following PFCs, most of which have for the first time been analytically separat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(146 reference statements)
0
6
0
Order By: Relevance
“…However, some slight emission gaps for global c -C 4 F 8 results were found before 2000. The average c -C 4 F 8 emissions from Droste et al, 2020 26 (15 Mt CO 2 -eq yr −1 over 1985–1988) and Oram et al, 2012 25 (15 Mt CO 2 -eq yr −1 over 1985–1988) were slightly higher than those from Mühle et al, 2019 24 [12 Mt CO 2 -eq yr −1 over 1985–1988 in CSIRO Inversion; 12 Mt CO 2 -eq yr −1 over 1985–1988 in Bristol Inversion], while c -C 4 F 8 emissions (1991–1998) from Droste et al, 2020 26 (5 Mt CO 2 -eq yr −1 ) and Oram et al, 2012 25 (5 Mt CO 2 -eq yr −1 ) were slightly lower than results of around 8 Mt CO 2 -eq yr −1 from both Mühle et al, 2019 24 and Mühle et al, 2022 23 . The c -C 4 F 8 datasets from more than one station (including Zeppelin, Mace Head, Jungfraujoch, Monte Cimone, Trinidad Head, Shangdianzi, Gosan, La Jolla, Ragged Point and so on) were employed in other studies 23 , 24 to derive c -C 4 F 8 emissions, while Oram et al, 2012 25 only used the c -C 4 F 8 dataset from Cape Grim to obtain the global TD c -C 4 F 8 emissions, which may explain the larger variability of its results.…”
Section: Resultsmentioning
confidence: 99%
“…However, some slight emission gaps for global c -C 4 F 8 results were found before 2000. The average c -C 4 F 8 emissions from Droste et al, 2020 26 (15 Mt CO 2 -eq yr −1 over 1985–1988) and Oram et al, 2012 25 (15 Mt CO 2 -eq yr −1 over 1985–1988) were slightly higher than those from Mühle et al, 2019 24 [12 Mt CO 2 -eq yr −1 over 1985–1988 in CSIRO Inversion; 12 Mt CO 2 -eq yr −1 over 1985–1988 in Bristol Inversion], while c -C 4 F 8 emissions (1991–1998) from Droste et al, 2020 26 (5 Mt CO 2 -eq yr −1 ) and Oram et al, 2012 25 (5 Mt CO 2 -eq yr −1 ) were slightly lower than results of around 8 Mt CO 2 -eq yr −1 from both Mühle et al, 2019 24 and Mühle et al, 2022 23 . The c -C 4 F 8 datasets from more than one station (including Zeppelin, Mace Head, Jungfraujoch, Monte Cimone, Trinidad Head, Shangdianzi, Gosan, La Jolla, Ragged Point and so on) were employed in other studies 23 , 24 to derive c -C 4 F 8 emissions, while Oram et al, 2012 25 only used the c -C 4 F 8 dataset from Cape Grim to obtain the global TD c -C 4 F 8 emissions, which may explain the larger variability of its results.…”
Section: Resultsmentioning
confidence: 99%
“…In cases where no updated information is available, global estimates were extrapolated from Vimont et al (2022), Western et al (2023) or other literature and were scaled to be consistent with those reported in AR6. Some extrapolations are based on data from the mid-2010s (Droste et al, 2020;Laube et al, 2014;Simmonds et al, 2017;Vollmer et al, 2018) but have an imperceptible effect on the total ERF assessed in Sect. 4 and are included to maintain consistency with AR6.…”
Section: Well-mixed Greenhouse Gas Concentrationsmentioning
confidence: 99%
“…In cases where no updated information is available, global estimates were extrapolated from Vimont et al (2022), Western et al (2023), or other literature and scaled to be consistent with those reported in AR6. Some extrapolations are based on data from the mid-2010s (Droste et al, 2020;Laube et al, 2014;Simmonds et al, 2017;Vollmer et al, 2018), but have an imperceptible effect on the total ERF assessed in Sect. 4, and are included to maintain consistency with AR6.…”
Section: Well-mixed Greenhouse Gas Concentrationsmentioning
confidence: 99%